Economic concentration and poverty in India - Dwivedi, D.N. (Delhi, 1974)
The biggest challenge being faced at present by India is the abject poverty and the destitution of more than 220 million of her people. The challenge is so gigantic and pressing that India's existence as a strong independent sovereign in the world community depends on whether or not the poverty of her masses is effectively eradicated. It is an admitted fact that India has achieved her political freedom but has utterly failed in salvaging herself from economic dependence. Owing to her failure on the economic front, her economic and political fate remained subordinated to the economic and political powers of the world. It is also an established fact that even billions and trillions of a starving people cannot make a strong nation. Therefore, if India is sincerely and genuinely interested in achieving her long cherished goal of being a strong, indepen dent nation, the problem of poverty will have to be solved prior to any other economic, social, and political problem.
Keywords: Poverty-India